2016
DOI: 10.1242/jcs.183772
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11 is a novel regulator of extracellular matrix synthesis and tissue mechanics

Abstract: We discovered that Cadherin-11 (CDH11) regulates collagen and elastin synthesis, both affecting the mechanical properties and contractile function of animal tissues. Using a Cdh11-null mouse model, we observed a significant reduction in the mechanical properties [Youngs' modulus and ultimate tensile strength (UTS)] of Cdh11 −/− as compared to wild-type (WT) mouse tissues, such as the aorta, bladder and skin. The deterioration of mechanical properties (Youngs' modulus and UTS) was accompanied by reduced collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 47 publications
6
65
0
Order By: Relevance
“…Specifically, gene expression of CyclinD1 increased by 3400‐fold, cyclin dependent kinases, CDK4, and CDK6 increased by 8‐ and 15‐fold, and transcription factors c‐MYC and E2F1 increased by 10‐ and 20‐fold, respectively (n = 3, P < .05). Interestingly, PDGFRβ gene expression increased by ~15‐fold and CDH11 by ~35‐fold upon CDH11 engagement, in agreement with previous work from our laboratory …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Specifically, gene expression of CyclinD1 increased by 3400‐fold, cyclin dependent kinases, CDK4, and CDK6 increased by 8‐ and 15‐fold, and transcription factors c‐MYC and E2F1 increased by 10‐ and 20‐fold, respectively (n = 3, P < .05). Interestingly, PDGFRβ gene expression increased by ~15‐fold and CDH11 by ~35‐fold upon CDH11 engagement, in agreement with previous work from our laboratory …”
Section: Resultssupporting
confidence: 91%
“…Recently we reported that deficiency of CDH11 results in impaired ECM synthesis by skin fibroblasts in vitro and in vivo . When we examined skin tissues from Cdh11 knockout ( Cdh11 −/− ) and WT mice, we found that the thickness of the dermis was significantly reduced in Cdh11 −/− mice (59 ± 8%, n = 4, P < .05) as compared to their WT counterparts (Figure A,B).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations